Potret Mahasiswi Berniqab di Universitas Islam Negeri Mataram : Kajian tentang Latar belakang dan Relasi Sosial - Mustain Mustain; Baehaqi (JURNAL PENELITIAN KEISLAMAN, 2022)
Stigmatic views on veiled women also appear in universities. Students with veiled are considered to have understanding and religious attitudes that are exclusive, radical, and intolerant. Especially after the National Counterterrorism Agency states that universities have been exposed to radicalism and terrorism, then a variety of responses have emerged, including a policy of prohibiting  students from wearing the niqab which in turn has caused controversy among the people. With a non-statistical quantitative approach, where data is collected through an open questionnaire, this study aims to understand the background that drives some female students at UIN Mataram to use the niqab, and the social relations they build with other female students who do not use the niqab. The results of this study indicate that female students who wear the niqab have a diverse secondary educational background, both from general and religious secondary education, to educational institutions that are traditional or conservative